PERILAKU KEKERASAN VERBAL DAN NONVERBAL DALAM RUMAH TANGGA: Studi Deskriptif pada Pemberitaan Ayah Penyiksa Anak Di Pondok Jagung Timur, Serpong Utara, Tangerang Selatan - Pramita Dewi (2023)
This study aims to determine the form of violence in the urban village of West Pondok Jagung, North Serpong, South Tangerang, by investigating the chronology of one of the cases, by Investigating the chronology of the facts of one of the existing cases, namely Father Child Abuser. Based on the disaggregated data of UPTD P2TP2A South Tangerang City in 2021, there are cases of violence, which are relatively higher in the South Tangerang area. The method used is a qualitative case study method with primary and secondary data. Data collection techniques through interviews and literature studies. Researchers used four stages of data analysis, according to Milles & Huberman, namely data collection, data reduction, and conclusion drawing or verification with data triangulation. The results of this study indicate that there are discrepancies in the chronology of the cases that occurred. Some sources state that the case is fake, while others think that this case happened. In addition, it was also found that the form of violence that occurred in the West Pondok Jagung Timur area, North Serpong, and South Tangerang was almost all violence, including violence in the form of crime that also occurred in the West Pondok Jagung area. In the form of crime that also occurred in West Pondok Jagung.